A Patient-centric Clinical Trial Design to Comprehensively Evaluate Low-Sodium Oxybate in People with Idiopathic Hypersomnia or Narcolepsy - Deborah A. Nichols; Teresa L. Steininger; Douglas S. Fuller; M. Todd Kirby; Emily C. Barker; Marisa Whalen; Jessica K. Alexander; Sarah Akerman; David T. Plante (Neurology and Therapy)
Abstract Introduction Low-sodium oxybate (LXB; Xywav®) is approved to treat idiopathic hypersomnia in adults and excessive daytime sleepiness or cataplexy in individuals aged ≥ 7 years with narcolepsy. The efficacy and safety of LXB have been demonstrated in randomized controlled trials. This study will comprehensively evaluate multiple daytime and nighttime symptoms in participants with idiopathic hypersomnia and participants with narcolepsy treated with LXB. Methods Jazz DUET (Develop hypersomnia Understanding by Evaluating low-sodium oxybate Treatment; NCT05875974) is a prospective, multi-cohort, multicenter, single-arm, open-label, interventional study. Establishing multiple cohorts across different diseases aligns with more generalizable research designs enabling a broader impact. Total study duration is ~ 10–21 weeks, which includes a 2- to 6-week screening period, an 8-day baseline period, a 2- to 8-week titration period, a 2-week stable-dose period, a 1- to 2-week end-of-treatment assessment period, and a 2-week safety follow-up period. To provide a robust dataset of changes with LXB treatment which will inform healthcare providers and their patients, DUET is administering a wide range of patient- and clinician-reported outcome assessments regarding symptom severity and daytime functioning and includes objective measures of sleep (ad libitum polysomnography protocol) and sleep inertia which have not been previously tested with this type of study design. Additionally, pharmacokinetics data and clinician titration feedback are collected to inform titration/dosing guidance for clinicians. DUET was designed in a patient-centric manner to reflect a real-world approach to conducting clinical trials. Planned Outcomes Using a patient-centric design aiming to address participants’ burden and improve their study experience, the DUET study will fill critical idiopathic hypersomnia and narcolepsy evidence gaps pertaining to sleep architecture (e.g., disrupted nighttime sleep) and response to LXB treatment, as well as provide data on outcomes that are meaningful to patients. Graphical abstract available for this article. Graphical Abstract